Description of supportive care and feasibility of physical exercise program to improve quality of life in advanced melanoma patients. Issue 3 (17th June 2023) - Boileau, Marie; Templier, Carole; Massip, Edouard; Dehoux, Clémentine; Dziwniel, Véronique; Fabre, Claudine; Thevenon, André; Mortier, Laurent
Abstract : Physical activity is the first-line treatment of cancer-related fatigue. It has shown benefits on patient's quality of life (QoL) when practiced during and after treatment. New treatments have drastically changed the prognosis of melanoma. Still, few data are available about research program of supportive care in advanced melanoma. The primary outcome was to assess the feasibility of setting up a prospective study evaluating the benefits of Adapted Physical Activity (APA) on the QoL of patients with advanced melanoma. Feasibility was defined with a combination of five criteria including completion of questionnaire, recruitment, participant retention, patient adhesion to supportive care, and absence of adverse event. Between September 2019 and March 2021, 271 melanoma patients were questioned. Around 60% of stage IV melanoma patients were interested in support care. Patient retention at 3 months was sufficient. Only one patient could not be evaluated after 3 months of enrolment because of deterioration of the general state. Adhesion to exercise and sessions was good. Supervised APA program appeared to be safe and well tolerated as no adverse events or discontinuations were reported. Setting up a prospective research program evaluating the benefits of physical activity in advanced melanoma patients seems feasible. With melanoma becoming a chronic disease, supportive care may reduce fatigue, improve QoL and help maintain a healthy lifestyle. Data supporting its benefits on this survivor population are needed.